Financial crises, sovereign risk and the role of institutions - Berlemann, Michael (Springer International Publishing Imprint: Springer, 2013)
The recent world economic crisis showed very clearly that financial crises and sovereign defaults are severe threats to economic and social prosperity. In addition, it became apparent that currency crises and banking crises often occur together and are closely related to sovereign debt crises and defaults. The present book contains new research on various important issues related to financial crises and sovereign default risk by leading experts in the field. The book discusses new modelling approaches to financial crises, defaults and their interdependencies. It also sheds light on the consequences of different sorts of crises for the trust in the institutions which are concerned with managing them. Moreover, it provides discussions of several institutional features of the EMU and the world financial system and in particular the risks inherent in these institutions. The book also includes interesting suggestions for solving crises and improving financial stability.